2020
DOI: 10.1080/14992027.2020.1832263
|View full text |Cite
|
Sign up to set email alerts
|

Uni- and bilateral spectral loudness summation and binaural loudness summation with loudness matching and categorical loudness scaling

Abstract: Objective: Current hearing aid prescription rules assume that spectral loudness summation decreases with hearing impairment and that binaural loudness summation is independent of hearing loss and signal bandwidth. Previous studies have shown that these assumptions might be incorrect. Spectral loudness summation was measured and compared for loudness scaling and loudness matching. Design: In this study, the effect of bandwidth on binaural summation was investigated by comparing loudness perception of low-pass f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
(71 reference statements)
0
5
0
Order By: Relevance
“…The RFR and GLM were applied to Bisgaard standard audiograms. These standard audiograms are well established and widely used for audiological investigations (e.g., Tu et al, 2021 ; van Beurden et al, 2021 ). They are based on a large clinical data base.…”
Section: Methodsmentioning
confidence: 99%
“…The RFR and GLM were applied to Bisgaard standard audiograms. These standard audiograms are well established and widely used for audiological investigations (e.g., Tu et al, 2021 ; van Beurden et al, 2021 ). They are based on a large clinical data base.…”
Section: Methodsmentioning
confidence: 99%
“…Regarding binaural loudness perception and fitting in hearing impaired (HI) listeners with conventional acoustic hearing aids, recent studies (Oetting et al, 2016;van Beurden et al, 2018van Beurden et al, , 2020 found a large variability of binaural broadband loudness perception in HI listeners after restoring the individual loudness perception of monaural narrowband signals due to frequency-dependent amplification. Ewert and Oetting (2018) introduced a loudness-based measurement procedure using a combination of narrowband sounds at equal loudness, enabling a direct comparison of loudness perception in NH and aided HI listeners.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that for some HI individuals, severe deviations from average loudness perception exist, likely causing problems in daily life and with hearing aids (Oetting et al, 2018 ; van Beurden et al, 2020 ). Even if only a subgroup of HI listeners is affected, loudness models that aim to support hearing aid fitting and development need to account for these listeners.…”
Section: Discussionmentioning
confidence: 99%
“…With bilaterally aided HI listeners, it has been shown that binaurally presented broadband stimuli are perceived louder by aided HI listeners than by NH listeners at high levels, i.e., the uncomfortable level perceived as “too loud” is reached at lower levels (Oetting et al, 2018 ; van Beurden et al, 2020 ). For monaural presentation, this effect is smaller (Strelcyk et al, 2012 ; Oetting et al, 2016 ; Ewert and Oetting, 2018 ).…”
Section: Introductionmentioning
confidence: 99%